2023
DOI: 10.1111/1365-2745.14099
|View full text |Cite
|
Sign up to set email alerts
|

Litter accumulation, not light limitation, drives early plant recruitment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 124 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…1f). Similarly, Jessen et al (2023) also reported that fertilization, independent of litter removal, significantly decreased the total number and richness of seedlings, likely because higher ammonium levels in fertilized plots could create a toxic environment for seedlings (Britto & Kronzucker, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1f). Similarly, Jessen et al (2023) also reported that fertilization, independent of litter removal, significantly decreased the total number and richness of seedlings, likely because higher ammonium levels in fertilized plots could create a toxic environment for seedlings (Britto & Kronzucker, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Similar to soil, leaf litter could also affect plant growth, species diversity and community structure (Liu et al, 2017; Ma et al, 2020; Olson & Wallander, 2002), thus playing important roles in population establishment and community dynamics (Jessen et al, 2023; Lamb, 2008; Xiong & Nilsson, 1999). However, related research has focused mainly on physical (e.g., maintaining soil moisture and temperature, increasing nutrition and reducing light) or chemical effects (e.g., releasing allelochemicals) (Demey et al, 2013; Jessen et al, 2023; Möhler et al, 2018; Zhang et al, 2017) but has rarely focused on leaf microbial effects. Until 2017, Whitaker et al (2017) extended the PSF to aboveground tissues (including leaf, stem and floral tissues), termed “plant‒ phyllosphere feedbacks (PPFs)”, and found that all four Asteraceae species experienced stronger negative PPFs than PSFs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to soil, leaf litter could also affect plant growth, species diversity and community structure (Liu et al, 2017 ;Ma et al, 2020 ;Olson & Wallander, 2002 ), thus playing important roles in population establishment and community dynamics (Jessen et al, 2023 ;Lamb, 2008 ;Xiong & Nilsson, 1999 ). However, related research has focused mainly on physical (e.g., maintaining soil moisture and temperature, increasing nutrition and reducing light) or chemical effects (e.g., releasing allelochemicals) (Demey et al, 2013 ;Jessen et al, 2023 ;Möhler et al, 2018 ;Zhang et al, 2017 ) but has rarely focused on leaf microbial effects. Until 2017, Whitaker et al (2017) extended the PSF to aboveground tissues (including leaf, stem and floral tissues), termed "plantphyllosphere feedbacks (PPFs)", and found that all four Asteraceae species experienced stronger negative PPFs than PSFs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to soil, leaf litter can also affect plant growth, species diversity, and community structure ( Liu et al, 2017 ; Ma et al, 2020 ; Olson and Wallander, 2002 ), thus playing important roles in population establishment and community dynamics ( Jessen et al, 2023 ; Lamb, 2008 ; Xiong and Nilsson, 1999 ). However, related research has focused mainly on physical (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation